DESAIN PEKERJAAN BAGIAN BINATU PADA HOTEL GRAND JATRA PEKANBARU - Emi Kurnia Putri; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Evolving an area make the business including increased. This is mareked with theestablishment of a luxury hotel, especially in Sumatra Riau in Pekanbaru. To provideaccommodation for tourist, many hotels are standing here like a five star hotels, one of thegrand jatra hotel Pekanbaru. This study aims to find out the job design and suitability of jobdesign laundry section Grand Jatra Hotel Pekanbaru. This research uses descriptive qualitativemethod to analyze problems based on data collection techniques of interview, observation, anddocumentation which then draw conclusion. Job design includes the division of labor and jobvariation to all staff. Sources of data from this research is obtained from the interview with allstaff of Laundry section Grand Jatra Hotel Pekanbaru. From the results of research conducted,it appears that the division of work is good but on the variety of work doesn’t seem appropriateKeywords: Job Design, Laundry, Employees